American heritage history of world war ii eaudiobook - Ambrose, Stephen E. (HighBridge Audio, 2017)
In planes and foxholes, in deserts and jungles, on ships and beaches, Ambrose shines a light on the people involved-the leaders, the fighters, the victims. With chapters on the atrocities of the Holocaust and revelations about the secret war of espionage, Ambrose's analysis also offers insight into the events that precipitated the Cold War.